Improvement of psychological adjustment in fibromyalgia subjects after a 4-weeks taoist qigong programme. - Manzaneque-Vázquez, Juan Manuel; Vera-Fernández, Francisca María; Rodríguez-Peña, Francisco Miguel; Sánchez-Montes, S.; Blanca-Mena, María José (My University, 2025)
Background: Qigong is an ancient Chinese psychosomatic exercise that exerts significant changes of psychobiological variables, and has been said to induce noteworthy physical and psychological benefits. Notwithstanding its clinical potential, qigong has been scarcely studied in fibromyalgia, and the specific effects of Taoist qigong in this syndrome are unknown. Since treatment of fibromyalgia remains a serious challenge, shedding light on the psychological action of Taoist qigong in these subjects is essential. Purpose: The present study was designed to explore whether Taoist qigong could improve psychological adjustment in fibromyalgia individuals after a short period of practice. Method: 39 individuals with fibromyalgia participated in the study, 16 in the experimental group and 23 in the control. Experimental subjects engaged in a four-weeks Taoist qigong training programme. To assess psychological adjustment, instruments such as the Depression Anxiety Stress Scales (DASS-21), the Negative and Positive Affect Scale (NAPAS), and the Life Satisfaction Scale (SWLS), were employed before and after the experiment concluded. Results: The experimental group displayed a significant improvement in anxiety, depression, and stress, including total distress. Likewise, a significant reduction of negative affect was also observed, although the positive affect component of this scale remained without changes, as did Life Satisfaction. Conclusions: The practice of Taoist qigong for a short period of one month induced a noteworthy improvement of several mood indexes in subjects with fibromyalgia. Qigong, therefore, may be a potential therapeutic tool in subjects with this syndrome.
Keywords: Medicina china; Fibromialgia; Psychological adjustment; Qigong; Fibromyalgia